KERAGAMAN KARAKTER FORMAL BANGUNAN FASILITAS PENDIDIKAN PENINGGALAN KOLONIAL BELANDA DI YOGYAKARTA - Jarwa Prasetya Sih Handoko (Asian Journal of Innovation and Entrepreneurship, 2015)
The phenomenon of damage colonial heritage buildings of historical value due to the unavailability of adequate references and data regarding the design of the dutch colonial buildings, especially the caracter of the building, so people often do not make the effort of preservation of the building. The need for any explanation of the formal character of the colonial heritage buildings for consideration in the designing of new buildings across the region. The need to do a study to dig and explore various aspect formal caracters of the colonial heritage building of educational facilities in Yogyakarta is the background of the need for this research study Keywords: Diversity, Formal character, Colonial Dutch.